VARIETAL ASSESSMENT, HERITABILITY AND CORRELATION ANALYSIS OF ADAPTATION- AND PRODUCTION-RELATED TRAITS IN BREAD WHEAT LANDRACES OF THE ALGERIAN SAHARA OASES - M. Boulacel; T. Hadji; A. Ghennai; M. Hadji; A. Benlahbib; N. Souilah; H. Bendif (مجلة الأنبار للعلوم الزراعية)
Wheat from the Algerian Saharan oases represent important breeding material for the development of genotypes resistant to environmental stress and climate change. This study was conducted on six Saharan oases bread wheat (Triticum aestivum L.) landraces using complete randomized block design. It evaluated their morphological, agronomical, physiological and phenological performance, and their related estimates of genetic variability and heritability under semi-arid conditions during the 2020/2021 growing season. Data were analyzed for correlation coefficient, path coefficient analysis, principal component analysis and cluster analysis. The results revealed the existence of significant variations in all measured traits. High heritability and high genetic advance were recorded for yield, yield-related traits, and most morphological traits including plant height, peduncle length, spike length, number of nodes, and flag leaf area. Additionally, analyses of correlation coefficients showed grain yield to be significantly correlated to yield-related traits, chlorophyll content, days to first leaf, days to booting and days to heading. Furthermore, path coefficient analysis showed direct positive effects of number of grains per spike, weight of thousand grain and days to booting on grain yield. Multivariate analysis enabled the study of the relationship between different traits while simultaneously aiding in the classification and selection of the highest yielding and best adapted landraces.